HAK PEREMPUAN PASCA PERCERAIAN : ANALISIS PERBANDINGAN HUKUM KELUARGA DI INDONEISA DAN DUNIA - Sadari, Sadari (STAIN Jurai Siwo Metro, 2015)
AbstractIslamic law has set universally regarding family law issues relating to divorce, but it seems that the difference for womens rights after divorce occurs in a range of applications in the side or the level of legal arrangements, given the differences in social system, cultural system or even the political system in each each country both in Indonesia and in the Islamic world. Comparative analysis of family law related to womens rights after divorce in this article, based on the exposure of legal jurisprudence schools and the positive law in force in countries such as Indonesia, Malaysia Tunisia, Iran, Egypt, Yemen, Turkey, and Iraq, special about the reasons of divorce. In general, these countries legal materials more dominant tendency is patterned Shafii schools. However, there are several different opportunities such as: in terms of the chances of divorce, in each country appears once judiciary complicate divorce, meaning to go keperceraian first sought peace efforts were made as strong as possible. Yet in terms of the position of the parties is protected rights before the law (principle of equality before the law) in each country for example in Indonesia and South Yemen, especially in Yemen has also strengthened in its National Constitution that